2014
DOI: 10.1111/bjd.13125
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial protein S100A7/psoriasin enhances the expression of keratinocyte differentiation markers and strengthens the skin's tight junction barrier

Abstract: Our finding that S100A7/psoriasin regulates differentiation and strengthens TJ barrier function provides novel evidence that, in addition to antimicrobial and immunoregulatory activities, S100A7/psoriasin is involved in skin innate immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 59 publications
3
57
1
1
Order By: Relevance
“…[42, 43] In human cultured keratinocytes, hS100A7 also induce the expression of several differentiation markers, which are overexpressed in psoriatic skin. [44, 45] In our study, we confirmed that mS100a7a15 was overexpressed in psoriasis model skin. Mature IL-1α, not IL-1β, is induced by hS100A7 stimulation in keratinocytes, and mature IL-1α is also detected in in vivo .…”
Section: Discussionsupporting
confidence: 81%
“…[42, 43] In human cultured keratinocytes, hS100A7 also induce the expression of several differentiation markers, which are overexpressed in psoriatic skin. [44, 45] In our study, we confirmed that mS100a7a15 was overexpressed in psoriasis model skin. Mature IL-1α, not IL-1β, is induced by hS100A7 stimulation in keratinocytes, and mature IL-1α is also detected in in vivo .…”
Section: Discussionsupporting
confidence: 81%
“…In addition, while Hattori et al . employed a high calcium concentration (1.25 m m ) to induce differentiation, we used a low calcium concentration (0.1 mM CaCl 2 ) and induced density‐dependent differentiation of keratinocytes in which epidermal differentiation markers such as KRT1 and KRT10 were increased (Fig. S2a).…”
Section: Discussionmentioning
confidence: 99%
“…55 Recent studies in cultured keratinocytes have also shown that other innate mediators, such as antimicrobial peptides (AMPs) including S100A7, LL-37 and HBD3 enhance TJ protein expression and TJ function (TER and macromolecule tracer permeability) thus contributing to repair and possibly even maintain homeostatic barrier function. [56][57][58] It is important to note that the aforementioned studies utilized bacterial-derived peptidoglycan or synthetic TLR2-ligands, in an otherwise "sterile" environment and these stimulations were done during TJ assembly (e.g., wound repair model or differentiation of keratinocytes). The situation can be quite different and more complex when using whole bacteria or when evaluating the effect in full thickness epithelium with fully mature TJs.…”
Section: Tj and Innate Immune Barriermentioning
confidence: 99%